Teacher Efforts to Handle Underachiever Students in the Intensive C&D Class 3 Learning Process at TMI Al-Amien Prenduan Sumenep Madura Academic Year 2023-2024 - Abdul Qadir Jailani; Hanan Mulyana (Values: Jurnal Kajian Islam Multidisiplin, 2024)
The findings in the research show that the underachiever experienced by female students in Intensive Class 3 is a problem that must be overcome. Underachievers are students who are unable to balance the material obtained in the learning process with the grades they produce. A state of physical and psychological fatigue experienced by a person over a long period of time which is characterized by physical, mental or emotional exhaustion. Underachiever behavior can occur in various educational settings, including Islamic boarding schools. Therefore, Islamic boarding schools as educational institutions must try to minimize this by maximizing the role of parties directly involved with female students, including teachers. The problem raised in this research is how underachievers occur in female students in class 3 of the Intensive TMI Putri Al-Amien, how to overcome them and the obstacles in overcoming them, which are explained in two focuses, namely: How teachers attempt to deal with underachiever students in the learning process of class 3 of Intensive C&D at TMI Al-Amien, and than What are the teacher's obstacles in dealing with underachiever students in the C&D Intensive Class 3 learning process at TMI Al-Amien and what are the solutions. This research uses a qualitative case study approach. Data sources were obtained from teachers, el-psycha and female students. The data collection methods used were observation, interviews and documentation. Data analysis is carried out by reducing data, presenting data, and drawing conclusions. Meanwhile, the technique used to check the validity of the data is technical triangulation. The results of this research are that underachievers that occur in Intensive Class 3 female students are caused by two factors, namely internal and external factors of the child. In this case, teachers play a very active role in overcoming it. The methods used by teachers include providing motivation and positive advice, warning, giving rewards, providing adequate rest time for their children and controlling the behavior of female students. The obstacles in overcoming them are internal and external factors.